The Application of Classroom Management in Teaching English at SMPN 1 Lilirilau - M, Andi Fitri Rahmasari; Abduh, Amirullah; Muhayyang, Maemuna (Celebes Journal of Language Studies, 2024)
The aim of this research is to highlight the ways of an English teacher managing classroom interaction at SMPN 1 Lilirilau, Soppeng. It utilized a case study research design with one seventh-grade English teacher as the subject of this research. The research instruments were an observation and interview to strengthen the data gain through the observation coming with three qualitative data analysis methods, namely data reduction, data display, and the verification of conclusions. The data analysis found the five key aspects of classroom management were utilized by the teacher in English classroom interaction, namely (1) physical classroom design, (2) rules and routines, (3) teacher-student relationship, (4) engaging instruction, and (5) discipline. The physical design of classroom involves a modified U-shape seating arrangement, fostering interaction; rules and routines emphasize attentive listening, hand-raising, and punctuality, with specific routines for movement and learning process; positive teacher-student relationship contributes to a comfortable class atmosphere facilitated by a number of interactive teaching methods and game-based learning; effective classroom discipline remains a challenge, with unresolved issues potentially disrupting learning. These findings effectively lead the teacher to manage the classroom interactively and to avoid having some disruptive behaviors of the students in learning English as a foreign language.